Analisis Determinan Atas Profitabilitas Bank Syariah Di Indonesia - Nabila Firdaus Iman; Umiyati Umiyati (Jurnal Akuntansi dan Keuangan Islam, 2022)
This study aims to analyze the effect of Sharia Compliance, Operating Efficiency Ratio (OER) and Finance To Deposit Ratio (FDR) on the Profitability of Islamic Banks in Indonesia. The period used used is 2016-2020. The population in this study is Islamic Commercial Banks. This study uses a quantitative approach. The sampling method used in this research is purposive sampling. The total sample selected is 7 samples of Islamic Banks that meet the criteria. The analysis technique used is panel data regression with Eviews 10 software. The results of this study indicate that Profit Sharing Ratio (PSR) has no significant effect on Return On Assets in Islamic Banks, Zakat Performance Ratio (ZPR) has a significant effect on Return On Assets of Islamic Banks, Islamic Income Ratio (IsIR) has no significant effect on Return On Assets in Islamic Banks, Operating Efficiency Ratio (OER) has a significant effect on Return On Assets of Islamic Banks, and Financing To Deposite Ratio (FDR) has no significant effect on Return On Assets in Islamic Banks.ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh Sharia Compliance, Operating Efficiency Ratio (OER) dan Finance To Deposite Ratio (FDR) terhadap profitabilitas Bank Syariah di Indonesia. Periode yang digunakan yaitu tahun 2016-2020. Populasi pada penelitian ini adalah Bank Umum Syariah. Penelitian ini menggunakan pendekatan kuantitatif. Metode pengambilan sampel yang digunakan dalam penelitian ini adalah purposive sampling. Total sampel yang terpilih adalah sebanyak 7 sampel Bank Syariah yang memenuhi kriteria. Teknik analisis yang digunakan adalah regresi data panel dengan sofware Eviews 10. Hasil penelitian ini menunjukkan bahwa Profit Sharing Ratio (PSR) tidak berpengaruh signifikan terhadap Return On Asset pada Bank Syariah, Zakat Performance Ratio (ZPR) berpengaruh secara signifikan terhadap Return On Asset Bank Syariah, Islamic Income Ratio (IsIR) tidak berpengaruh signifikan terhadap Return On Asset pada Bank Syariah, Operating Efficiency Ratio (OER) berpengaruh secara signifikan terhadap Return On Asset Bank Syariah, dan Financing To Deposite Ratio (FDR) tidak berpengaruh signifikan terhadap Return On Asset pada Bank Syariah